The Possibilities of applying present-day Knowledge of Wine Aroma Components: Influence of several Juice Factors on Fermentation rate and Ester Production during Fermentation - Houtman, A. C.; Marais, J. (South African Journal of Enology and Viticulture, 2017)
The influence of several juice factors on fermentation and ester production was investigated to achieve a more satisfactory reproducibility of wine aroma composition. The contents of two acetates and three ethyl esters in the wine were used as the main analytical criteria. The factors which exerted the most marked influence on ester composition and fermentation were grape maturity, sugar content, fermentation temperature, and jutc’e>cfarity. The cuitivars examined exerted no noticeable differences.